Mast Cells in Cardiac Remodeling: Focus on the Right Ventricle - Argen Mamazhakypov; Abdirashit Maripov; Akpay S. Sarybaev; Ralph Theo Schermuly; Akylbek Sydykov (Journal of Cardiovascular Development and Disease, 2024)
In response to various stressors, cardiac chambers undergo structural remodeling. Long-term exposure of the right ventricle (RV) to pressure or volume overload leads to its maladaptive remodeling, associated with RV failure and increased mortality. While left ventricular adverse remodeling is well understood and therapeutic options are available or emerging, RV remodeling remains underexplored, and no specific therapies are currently available. Accumulating evidence implicates the role of mast cells in RV remodeling. Mast cells produce and release numerous inflammatory mediators, growth factors and proteases that can adversely affect cardiac cells, thus contributing to cardiac remodeling. Recent experimental findings suggest that mast cells might represent a potential therapeutic target. This review examines the role of mast cells in cardiac remodeling, with a specific focus on RV remodeling, and explores the potential efficacy of therapeutic interventions targeting mast cells to mitigate adverse RV remodeling.